Recent Existing Condition on Shrimp Culture at Jepara Coast, Central Java - Tita Elfitasari (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2006)
The shrimp culture is collapsing at Jepara coast. Several internal and external reasons have  caused this and are needed to be handled seriously. An alternative solution should be conducted and applied without delay. Recent Existing condition of the shrimp culture at Jepara Coast is  experiencing a tremendous decline in the last five years. There are four category of internal  factors determinant which shows this decline:  the  development  of  shrimp  culture production,  the  development  of  shrimp culture  available cultivation area, shrimp culture number of units,  and the development of the farmers’ internal revenue. The degradation of the shrimp culture at Jepara coast is mainly caused by environmental and managerial reasons. The environment is no longer supporting the shrimp culture at Jepara coast and to overcome this, a  relocation  or  re-zonation  should  be  applied.  As  alternative  solution,  to regain  the  Jepara region’s aquaculture potencies, a new species can be introduced and applied. In order to develop new species and to sustain its productivity, the new species should have some characteristics as  follows: easy to culture, invulnerable to disease, high market demand, high market price, short cultivation period, low production cost, and able to adapt with unfortunate water quality.   Key words : Shrimp culture condition, Jepara coast